Detection of pest through X-ray imaging: Application in Arabica Coffee Plant (Coffea arabica L.) - Sandesha, K.; Sandesha, Swetha (IJRDO-Journal of Applied Science, 2017)
Arabica coffee plant are generally affected by various pests. The Xylotrechus quadripes (Chevrolat), the coffee white stem borer (CWSB) is a very harmful pest as its grub feeds on the internal parts of the stem leaving very little external evidence of damage to the host plant at the initial stage. Existing pest management methods suffer from the lack of knowledge about the precise location of the pest within the plant and the extent of internal damage. Minimally invasive investigation of pest CWSB in the plant body has good potential to elucidate the stages of the pest infestation inside the stem and the plant growth. Digital radiography (X-ray imaging) is used for in situ feasibility studies of plant growth in presence or absence of pest and also helps in the early detection of the pest. These techniques has challenges like, to study the imaging in the live plants addressing to environmental conditions, X-ray imaging time and distance covered with respect to plant height. In this study, the use of digital radiography involves the mechanism where X-ray auto detection mode with cassettes detects X-rays at the time of exposure and automatically enters the image detection mode and then the image construction mode. Six uprooted stem of Arabica coffee plants were successfully scanned for CWSB. Results of X-ray imaging confirmed the presence of pest inside the coffee stem in varied stages of growth and even the exit holes of the matured pest were also observed clearly when exposed to the radiation. The advantage of using the digital radiography to study the severity of pest in the plant was investigated and discussed.